COMBINED PAPILLECTOMY AND AUTOLOGOUS CONJUNCTIVAL MEMBRANE GRAFT AS MANAGEMENT FOR SEVERE, REFRACTORY PALPEBRAL VERNAL KERATOCONJUNCTIVITIS: A CASE REPORT: Poster Presentation - Case Report - Ophthalmologist - ANNISA, DEVINA NUR; SUHARKO, HERNAWITA; GAOL, HASIANA LUMBAN (Majalah Oftalmologi Indonesia, 2023)
Introduction : Vernal keratoconjunctivitis (VKC) is a type of allergic conjunctivitis which often occurs repeatedly and chronically. It is unusual compared to other types of conjunctivitis due to its giant papillae (GP) manifestation that may cause serious complication on cornea and eventually lead to permanent vision loss. We present a surgical treatment—resection of GP—in conjunction with autologous conjunctival membrane graft to manage a severe case of VKC. Case Illustration : An 18-year-old male came with a prior history of recurrent acute allergic keratoconjunctivitis since seven years before. His GP had caused shield-like ulcer, which leads to corneal scar and interferes with his visual acuity. He also had mechanical ptosis due to the giant cobblestones. His symptoms were then managed by performing combined papillectomy and autologous conjunctival membrane graft. Discussion : During surgery, the GP on both of his eyes were excised until tarsus was visible. Autologous conjunctival membrane was grafted from superior quadrant of each eye, and sutured tightly onto the excised tarsus. Six month postoperatively, his superior tarsal conjunctiva remain relatively smooth, with well-controlled symptoms of keratoconjunctivitis. Conclusion : Combined papillectomy and autologous conjunctival membrane graft can be considered as an adjunctive intervention to medications, in patients with severe, refractory cases of palpebral vernal conjunctivitis. It can alleviate symptoms and reduce the possibility of permanent damage on corneal tissue.